Erratum: Hidden transition in multiferroic and magnetodielectric CuCrO2 evidenced by ac-susceptibility. (7th July 2017) - Shukla, Kaushal K.; Pal, Arkadeb; Singh, Abhishek; Singh, Rahul; Saha, J.; Sinha, A. K.; Ghosh, A. K.; Patnaik, S.; Awasthi, A. M.; Chatterjee, Sandip
Abstract: Original article: EPL, 118 (2017) 27008 .